Pabrik Gula Comal Baru: Perannya dalam Perkembangan Ekonomi dan Sosial Di Kabupaten Pemalang - Andhika Pramudya Wilantara (Universitas Negeri Semarang, 2024)
Abstract: This article examines the role of the Comal Baru Sugar Factory in the social and economic development of Pemalang Regency, Central Java, since its establishment in 1833. Through historical analysis and socio-economic theories, this study reveals how the sugar factory has changed the social and economic landscape of the region. The sugar factory not only became a major source of employment, but also triggered urbanization, changed social structures, and introduced new socio-cultural dynamics. However, behind its positive impacts, sugar industrialization also caused problems such as social inequality, labor exploitation, and environmental damage. This study highlights the complexity of the impact of industrialization on rural communities and the importance of understanding history to design a better future.